Hookworms and the vascular endothelium - Souadkia, Nahed (2010)
Background. Necator americanus is one of the major causes of human hookworm infection, affecting over 800 million people worldwide. Hookworm infections cause gastro-intestinal bleeding, anaemia and iron deficiency, and are associated with high rates of morbidity, especially in children. Although chemotherapy has proven effective, high rates of reinfection are reported in socioeconomically developing countries, possibly due to the short-term efficacy of anthelmintic drugs in addition to individual predisposition to these infections, raising interests in developing suitable alternatives to chemotherapy which are capable of providing complete, long-term protection against hookworms. Understanding of the molecular mechanisms used by Necator americanus larvae to penetrate the human skin and the vasculature would therefore aid the development of effective vaccines against this important pathogen.